Wearable Sensors: Applications and Challenges - Mahesh Kumar (Innovations in Science and Technology: Shaping a Sustainable Future (Vol. 1), 2024)
Health monitoring, diagnosis, and patient care have undergone revolutionary changes as a result of the use of wearable sensors in the medical field. This chapter examines the technological foundations of wearable sensors, showcasing their many features, which include bioimpedance sensors, electromyography, accelerometers, and heart rate monitors, etc. The potential for ongoing and individualized health monitoring is highlighted by discussing applications in the healthcare field, such as early illness identification, remote patient monitoring, and chronic disease management. Although the future seems bright, broad use will require overcoming obstacles including maintaining accuracy, handling privacy issues, and managing regulatory restrictions. In the future, wearable sensor capabilities might be further enhanced by combining new technologies like artificial intelligence and augmented reality with sensor technology improvements.